Decoloración de aguas residuales textiles utilizando el hongo ligninolítico anamorfo R1 de Bjerkandera sp. (2011)
ABSTRACT: Decolorization of synthetic and industrial wastewaters from textile industry by the anamorph R1 of white rot fungi Bjerkandera sp. was evaluated. The presence of NaCl and Na2CO3 wastewater concentration and treatment with non-sterile wastewater on decolorization were analyzed. In addition, the decolorization effect on wastewater toxicity was analyzed with Vibrio fischeri as target microorganism. The presence of salts in the treatment increased the lignin peroxidase activity from 5 to 20 U/L, without detriment of manganese peroxidase activity which remained at 70 U/L, also. The presence of salts also enhances dye adsorption degree over fungi biomass, improving the decolorization by the two mechanisms, degradation and adsorption. In hipersaline synthetic wastewater, the percentage of decolorization was 75%. The decolorization treatment of sterile textile effluents reached 65% in 8 days and the toxicity reduction was 58% with respect to untreated textile effluents. In non-sterile textile effluents, only 40% of decolorization was obtained. The presence of contaminant microorganisms which compete by substrate and increase pH by fungus metabolism, were likely the main causes of low decolorization.